Al-Azhar Calligraphy Sdn Bhd / Hairmanshah Idris Shaari... [et al.] - Idris Shaari, Hairmanshah; Ibrahim, Mohd Nasir; Nizam Ismail, Mohd Syahrul; Sulaiman, Muhammad Izwan; Ismail, Norham (2000)
Al-Azhar Calligraphy Sdn Bhd is the name of the company that mean the beautiful of arts, handwriting and calligraphy in Islamic. 'Al-Azhar' is taken from Arabic that means flowers. The concept is the beautiful Islamic arts and calligraphy in Islam. Main activities of this company was manufacturer and selling of glass etching and cooper tooling Islamic Calligraphy. This business was started on 1 January 2001. This business was located at Sungai Petani Kedah.